The Development Research on Hand-Puppets in âCita-Citakuâ Theme for the Fourth Grader of SDN Gotputuk Blora - Cahyadi, Fajar; Untari, Mei Fita Asri (Proceeding of International Conference on Teacher Training and Education, 2016)
There are some media which can be used in the teaching - learning process. One of them is hand-puppets. This media is different from the other hand-puppets because it is made personally for each theme, and here the researchers focused on the theme âCita-Citakuâ. This media is simple, economic, and efficient to be played. These media can also attract and build young learnersâ imagination, because it is made from colourful-attractive fabric, like flannel. This study focuses on the implementation of hand-puppets as teaching media in âCita-Citakuâ theme for the fourth grader of SDN Gotputuk Blora, Central Java. This theme of teaching material is so important to be taught to the students so that they can understand well how to reach their dreams in the future. It is an R&D research. The data were collected by interviewing, giving tests, and observing the teachers and students, and taking the documentation. Based on the collected data, the studentsâ scores of the implementation of hand-puppets in âCita-Citakuâ theme were increased. The students characters on self-confidence, teamwork, hard-work, and curiosity were increased positively too. The suggestion to the teachers is they must be a facilitator, motivator, and innovator to the students. They must motivate their students to ask and give an opinion. For the next researcher(s), we suggest them to make the similar research about hand-puppets in different field and theme.